Jimmy P. [videorecording (DVD)] : psychotherapy of a Plains Indian - Desplechin, Arnaud; Toro, Benicio del, 1967-; Amalric, Mathieu, 1965-; McKee, Gina, 1964-; Devereux, George, 1908-1985
Jimmy Picard, a Native American Blackfoot who fought in France during WWII, is admitted to Topeka Military Hospital in Kansas, an institution specializing in mental illness. Although he does not suffer any psychological causes for his painful symptoms, he is diagnosed as schizophrenic. Nevertheless, the hospital management decides to seek the opinion of Georges Devereux, a French anthropologist, psychoanalyst and specialist in Native American culture.